Introduction: NYAWA Light - Muhammad Noor, Ahmad Shukri (Universiti Putra Malaysia Press, 2017)
NYAWA is back in its sixth edition with the theme LIGHT. Throughout the ages, light has been valued as the most beautiful phenomenon of creation and the eye that perceives it as the most important human organ of sense perception. Its presence is essential for the most rewarding perception of almost all art. With the advancements made in lights and display technology nowadays, there is no better time than the present for NYAWA to explore the mystical, yet beautiful wonders of light, whether it be seeing shadows with the naked eye or observing fireflies through an application from a mobile gadget. Through scientific experimentation in the form of art, NYAWA provides scientists with a revolutionary way to educate visitors about the many functions of light and its significance to human life.